Perancangan Website UMKM Barak Ummy Menggunakan Aplikasi Visual Studio Code Untuk Pengembangan Pemasaran Dan Promosi jasa - Riska Mutmainah; Audy dwi Guna kencana putri; Arvan Adha (CV. ITTC INDONESIA, 2024)
The influence of current technology can change the marketing strategies of all business people. Where the right business strategy in this advanced era will advance the business. This encourages business people to adopt innovative marketing strategies, especially through online media. This article documents the design and implementation of an e- Commerce website for MSMEs offering gifts and hampers, focusing on the case study